The Youth Throwing Score: Validating Injury Assessment in Young Baseball Players. Issue 7 (18th July 2016) - Ahmad, Christopher S.; Padaki, Ajay S.; Noticewala, Manish Suresh; Makhni, Eric Chugh; Popkin, Charles Aaron
Objectives: Epidemic levels of shoulder and elbow injuries have been reported in youth and adolescent baseball players. Despite the concerning frequency of these injuries, no instrument has been validated to assess upper extremity injury in this patient population. The purpose of this study was to validate an upper extremity assessment tool specifically designed for youth baseball players. We hypothesize this tool will be reliable, responsive and valid. Methods: The Youth Throwing Score (YTS) was constructed by a multidisciplinary healthcare provider team in addition to baseball coaches as a tool to assess upper extremity injury in 10 to 18 year old baseball players. The instrument was comprised of a demographics section and a 14 item assessment of pain, fatigue and psychosocial health. The 14 items were scored from 1 to 5 and weighted equally, with higher scores reflecting fewer symptoms and less functional disability. The psychometric properties, including the test-retest reliability, internal consistency, and responsiveness were calculated. Additionally, the Pearson correlation coefficient to 4 validated outcomes was determined. Results: A pilot form of the instrument was administered to 25 players to assess comprehension and mean item importance. Pilot analysis resulted in none of the 14 items receiving less than a 3 out of 5 mean athlete importance rating and the final instrument read at a Flesch-Kincaid level of 4.1, appropriate for patients age 9 and older. A total of 223 players completed the Youth Throwing Score, with an average player age of 14.3 ± 2.7 years old. The players self-assigned injury status, resulting in an average survey score of 59.7 ± 8.4 for the 148 players 'playing without pain, ' 42.0 ± 11.5 for the 60 players 'playing with pain, ' and 40.4 ± 10.5 for the 15 players 'not playing due to pain.' Players playing without pain scored significantly higher than those playing with pain (p < .001). The scoring tiers of the Youth Throwing Score are displayed in Figure 1. Additionally, players who had suffered throwing arm injuries (P < .001) and players who has undergone throwing arm surgeries (P = .039) scored significantly lower on the YTS. Finally, players who participated in both their school and club teams scored lower than those who only played for either their school or club teams (P < .001). Psychometric analysis showed a test-retest intraclass correlation coefficient of 0.90 and a Cronbach alpha intra-item reliability coefficient of 0.93, indicating excellent reliability and internal consistency. Pearson correlation coefficients of 0.65, 0.62, and 0.31 were calculated between the YTS and the Pediatric Outcomes Data Collection Instrument Sports/Physical Functioning Scale (PODCI), Kerlan Jobe Orthopaedic Clinic Shoulder and Elbow Score (KJOC), and the Quick Disabilities of the Arm, Shoulder and Hand Score (QuickDASH). Injured players scored an average of 9.4 points higher following treatment (P < .001) and players who improved in their self-assigned pain categorization scored 16.5 points higher (P < .001). The statistical properties of the Youth Throwing Score are summarized in Table 1. Conclusion: The Youth Throwing Score is the first valid, reliable and responsive instrument designed for assessing young baseball players' upper extremity health. Its robust psychometric properties indicate its potential in assisting physicians care for injured throwers.